Selling to the government : what it takes to compete and win in the world's largest market - Amtower, Mark. (Hoboken, N.J. : Wiley, 2011)
'Learn the crucial ins and outs of the world's largest market The U.S government market represents the largest single market-anywhere. Government contract tracking firm Onvia estimates that government business-federal, state, local and education-represents better than 40% of the nation's GDP. While anyone can play in this market, only those with the right preparation can win. Selling to the Government offers real-world advice for successful entry into the biggest market anywhere. Get proven approaches, strategies, tactics, and tools to make your business stand out, build relationships, understand procedures, and win high-stakes contracts. Every year thousands of companies enter the massive U.S. Government (BtoG) marketplace, and by the end of the first year, most are gone and less than 10% make it to year two Author has advised hundreds of companies, including Apple, Dell, CDW, Northrop Grumman, General Dynamics, IT, GTSI, and many small firms, on all aspects of marketing and selling to the government From the go/no-go decision, through company infrastructure requirements, marketing, sales, business development, and more, this book offers the best advice from the most recognized authority in the market.'--
Includes index.
Keywords: Public contracts -- United States; Government contractors -- United States; Government purchasing -- United States